Investigation of the Influence of Ni Doping on the Structure and Hardness of Ti-Ni-C Coatings. (6th July 2017) - Daniel, J.; Souček, P.; Bernátová, K.; Zábranský, L.; Stupavská, M.; Buršíková, V.; Vašina, P.
Abstract : Nanocomposite nc-TiC/a-C:H thin films exhibit unique combination of mechanical properties, high hardness, low friction, and wear. Selective doping by weak-carbide forming element can be used in order to specifically design the physical and chemical properties of nc-TiC/a-C:H coatings. In this paper we report on an effect of nickel addition on structure and hardness of the nc-TiC/a-C:H coatings. The effect of Ni alloying on the coating structure under conditions of DCMS and HiPIMS depositions was studied. The coating structure was correlated with the coating hardness. The grain size, the grain carbon vacancy concentration, and the mean grain separation were found to be the key parameters determining the coating hardness. Ni doping proved to have a significant effect on the coating microstructure which resulted in changes of the hardness of the deposited coatings.